ENTREPRENEURIAL ECOSYSTEM IN THE REPUBLIC OF MOLDOVA: THE ROLE OF GOVERNMENT POLICY - CIRLAN, Ana (Economy and Sociology, 2021)
The article presents and analyses the entrepreneurial ecosystem in the Republic of Moldova, as a solution for an integrated approach to the problems of entrepreneurs. Entrepreneurial ecosystems represent a set of interdependent actors and coordinated factors so as to increase the productivity of SMEs. The paper includes: (I) investigating the literature on entrepreneurial ecosystems; (II) analysis of the role of public policies in creating and supporting entrepreneurial ecosystems; (III) finalizing the components of the entrepreneurial ecosystem in the Republic of Moldova and performing their evaluation through the prism of international rankings. The aim of this research is to elucidate the role of entrepreneurial policies with a holistic approach to the creation of the entrepreneurial ecosystem. The key challenge for the authorities is to identify the pillars that contribute to the development of an ecosystem. However, the existence of a large number of entrepreneurial support programs and projects does not necessarily lead to a qualitative increase in the number of enterprises. The results of the research showed that the authorities promote policies to support the business environment with a fragmented approach and an emphasis on increasing quantitative indicators. At the same time, the analysis of the components of the entrepreneurial ecosystem in the Republic of Moldova, through international rankings, indicates the deterioration of the business environment conditions. The research methodology is based on the analysis of policy documents on SME support and data provided by reports of international organizations (World Bank, World Economic Forum, Organization for Economic Cooperation and Development, etc.).